Pengaruh Hedonic Motivation, Lifestyle, dan Fear of Missing Out (FoMO) terhadap Impulse Buying Produk Jims Honey pada Konsumen Shopee di Kota Kalianda : Penelitian - Laila Farhatun; Herwanto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
In today's digital era, the internet has become an inseparable part of everyday life. In this increasingly developing digital era, consumer behavior has undergone significant changes, especially in online shopping habits such as shopping for Fashion products through Shopee E-commerce. This study aims to determine the effect of Hedonic Motivation, Lifestyle, and Fear of Missing Out (FoMO) on Impulse Buying of Jims Honey products on Shopee consumers in Kalianda City. The research method used is a Quantitative method by distributing questionnaires via Google Form. The population and sample used are 152 respondents from the community in Kalianda City, the technique used in sampling is Non-Probability Sampling with Purposive Sampling. Data sources come from primary data and secondary data. The analysis used was Instrument Test, Classical Assumption Test, Multiple Linear Regression Test, Multiple Correlation Test, Determination Coefficient Test and Hypothesis Test using SPSS version 25 application. The results obtained stated that the Hedonic Motivation (X1), Lifestyle (X2) and Fear of Missing Out (FoMO) (X3) variables were proven to have a positive and significant effect on the Impulse Buying (Y) variable of Jims Honey Products on Shopee Consumers in Kalianda City.